Lights Out: Conserving Electricity for War in the Canadian City, 1939-1945 - Evenden, Matthew (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2005)
Economic mobilization in Canada during the Second World War drove a major expansion in power demand in cities of the industrial heartland. To meet the needs of wartime industry, the federal government imposed power conservation measures, and utilities sought to inspire voluntary conservation among urban and primarily female consumers. These measures produced conflicts over their proper application and broader meanings. Conservation came to be understood not as an environmental measure, but as a planning policy to restrict uses in some sectors of society to allow for unfettered use in others. Wartime conservation did not ultimately reduce power demand in Canada, but it did lay down conditions that would support massive postwar growth.